Movement analysis and metabolic profile of tennis match play: comparison between hard courts and clay courts - Ponzano, M.; Gollin, M. (International Journal of Performance Analysis in Sport, 2017)
This study aimed to define the movement analysis and metabolic model in tennis on hard courts and clay courts. Twenty-four tennis players were equipped with a 15 Hz GPS and a Polar. H7 and played a match on each playing surface. The average duration of matches was 76 Å} 24 (C) and 69 Å} 17 min (H). The maximum heart rate (HRmax) was 185 Å} 14 (C) and 178 Å} 10 bpm (H), the average heart rate (HRav) was 144 Å} 14 (C) and 139 Å} 12 bpm (H). The average metabolic power (MPav) was 3.93 Å} .34 (C) and 3.70 Å} .34 W Å~ kg-1 (H) (ES = .72, C > H, +6%). The ANOVA and the post hoc showed significant differences regarding the considered parameters on both the surfaces. The t-test highlighted significant surface-related differences (ES = .88, C > H, +26%) concerning accelerations performed between 50 and 60% of the maximum value, decelerations between 40 and 50% of the maximum (ES = 1.28, H > C, +37%), metabolic power between 0 and 10 W Å~ kg-1 (ES = .71, H > C, +1%), and 10 and 20 W Å~ kg-1 (ES = .78, C > H, +15%).